Exploring Frankl’s meaning, purpose and value of life in Malaysian university students - Ab Razak, Ratna Roshida; Adnan, Zatul Himmah; Ku Samsu, Ku Hasnita; Muhammad, Zarina; Lee, Yoke Fee (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
This study has been using the Logotherapy approach, a therapy introduced by Viktor Frankl that emphasizes the meaning, purpose and value of life. Frankl’s concept of purpose in life is based on a religious existential foundation which postulated that the essence of human motivation is the will to meaning. Frankl asserted that under any circumstance, there is a seed of meaning. (Frankl, 1997). The main purpose of this exploration study is to identify the meaning, purpose and value in life among university students in Malaysia. Based on Frankl’s (1953) theory of purpose in life, Crumbaugh and Maholick (1964) developed the Purpose in Life Test (PIL) to measure the degree a person experiences a sense of meaning, purpose and value in life. This Purpose in Life Test (PIL) was psychometrically analyzed using a total number of 2586 university students to quantify the existential concept of meaning, purpose and value in life. Analysis of the data presented evidence that the Purpose in Life (PIL) test could be a larger dimension as well as being a scale in itself. The PIL showed a good internal consistency (Alpha= 0.930) and factor analysis revealed three factors which were categorized as Excitement of Life, Contentedness with life and Purpose and Goals in Life.